2012
DOI: 10.1107/s1600536812026682
|View full text |Cite
|
Sign up to set email alerts
|

Tetraaquabis(thiourea-κS)cadmium(II) triaquatris(thiourea-κS)cadmium(II) disulfate

Abstract: The title compound, [Cd(CH4N2S)2(H2O)4][Cd(CH4N2S)3(H2O)3](SO4)2, contains two mol­ecules of each of the Cd complexes and four sulfate ions in the asymmetric unit: all the Cd atoms exhibit distorted octa­hedral geometries. The Cd—S and Cd—O bond lengths around the Cd atoms in the bis­(thio­urea) cations are in the ranges 2.580 (4)–2.599 (4) and 2.323 (8)–2.421 (9) Å, respectively, and the S atoms are in a cis orientation. In the tris­(thio­urea) cations, the corresponding bond lengths around the Cd atoms are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The crystal structure of a hydrated cadmium thiourea sulfate showed both cis -[Cd(TU) 2 (H 2 O) 4 ](SO 4 ) and fac -[Cd(TU) 3 (H 2 O) 3 ](SO 4 ) complexes co-crystallized in the unit cell, with the mean Cd-S (Cd-O) bond distances 2.59 (2.37) Å and 2.62 (2.41) Å, respectively. 52 A mean Cd-S distance of 2.53 ± 0.02 Å is expected for a [Cd(TU) 4 ] 2+ complex from EXAFS, as obtained for the solid [Cd(TU) 4 ](NO 3 ) 2 compound (Table 5 and Figure S-7). …”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The crystal structure of a hydrated cadmium thiourea sulfate showed both cis -[Cd(TU) 2 (H 2 O) 4 ](SO 4 ) and fac -[Cd(TU) 3 (H 2 O) 3 ](SO 4 ) complexes co-crystallized in the unit cell, with the mean Cd-S (Cd-O) bond distances 2.59 (2.37) Å and 2.62 (2.41) Å, respectively. 52 A mean Cd-S distance of 2.53 ± 0.02 Å is expected for a [Cd(TU) 4 ] 2+ complex from EXAFS, as obtained for the solid [Cd(TU) 4 ](NO 3 ) 2 compound (Table 5 and Figure S-7). …”
Section: Discussionmentioning
confidence: 62%
“…We are unable to ascertain the degree of hydration m in the [Cd(TU) 3 (H 2 O) m ] 2+ complex, which is a minor species in solution according to the stability constants (Figure S-1), but propose that the [Cd(TU) 3 (H 2 O) 3 ] 2+ complex is formed, as in the crystal structure. 52 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, polymeric species are formed through bridging sulfur or nitrogen atoms [21,[24][25][26][27][28][29], e.g., [Cd(Metu) 2 (SCN) 2 ] n [24] and [Cd(Imt) 2 (SCN) 2 ] n [25]. [31]. The complexes with a Cd:thione ratio of 1:4 may be ionic or nonionic.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the highest binding capacity was observed for imprinted polymer, which was produced from 1-allyl-2-thiourea (M4) ( Table 2). Based on the literature data [18][19][20], we could suppose that 1-allyl-2-thiourea (M4), the monomer which possesses thiocarbonyl group, can strongly interact with cadmium(II) ions. The interactions between thiourea and cadmium(II) ions by X-ray diffraction method [18] as well as the properties of triallylthiourea cadmium chloride crystals by infrared spectroscopy and thermogravimetry were investigated [19,20].…”
Section: Effect Of Functional Monomer On Binding Capacity Of Cadmium(mentioning
confidence: 99%